Podział wyniku finansowego - dochód stawiany do dyspozycji właścicieli a dochód należny właścicielom - Wrońska, Elżbieta Maria (The Source of the Dividend - Net Profit Versus Free Cash Flow to Equity, 2008)
The article refers to dividends. A dividend is money paid by a company to its shareholders. This means that it is an income for shareholder and at the same time it is a cost for the company. The dividend is a form of distributing firm's cash. The basis of counting dividends is the company's earnings (net profit) but the source of paying out is free cash flow to equity. It is possible that dividends can be higher or lower than cash flow. The purpose of this research is to examine the relation among dividends, net profit and cash flow. The research was carried out among 7 employee owned companies and among 9 public limited companies. The outcome of this research shows that both groups of the firms do not have money (free cash flow to equity) to pay out dividends. However, employee-owned companies do not pay dividends, while public firms pay dividends.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 607-614